Benefits of the Pilates method on the quality of life of the elderly - Andrade, Jéssica de Oliveira; Castro, Juçara Gonçalves de; Coelho, Bruna Nádya Lopes da Silva (Revista de Casos e Consultoria, 2021)
Aging results in functional losses that compromise the individual’s ability to master the execution of their daily activities, leading to reduced quality of life. The Pilates method promotes a better physical and mental conditioning of the individual and, as a consequence, increases the quality of life, thus becoming a low-impact physical activity alternative for the elderly. The aim of this research was to analyze the effects of inserting the Pilates method on the quality of life of the elderly. This is a bibliographic research through an integrative literature review, with a descriptive character. The research took place in September and October 2021, in the following databases: National Library of Medicine (PubMed), Latin American and Caribbean Literature in Health Sciences (LILACS) and Medline through the Virtual Health Library (VHL), in September and October 2021, using the following Health Descriptors (DesCS): Pilates; Aged; Quality of life. These keywords were related to the Boolean operator “AND”. 89 articles were found; after applying the inclusion and exclusion criteria, 5 publications were selected for the development of the integrative review. The studies found analyzed the quality of life of the elderly from the implementation of the Pilates method in their routine. The identified effects benefited the lung, psychological and physical capacity of this population. It was observed that the Pilates method reduces the functional and social degradation of the elderly, providing for increased autonomy, in order to significantly raise the quality of life indices.